The impact of policy interactions on the recycling of plastic packaging waste in Germany - Carsten Gandenberger; Robert Orzanna; Sara Klingenfuß; Christian Sartorius (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
Due to the environmental challenges associated with the strong growth of plastic waste worldwide, the EU Commission recently published a green paper on a European Strategy on Plastic Waste in the Environment (COM (2013), 123 final), which highlights the challenges and opportunities that arise from improving the management of plastic waste in the EU. The European Waste Directive (2008/98/EC) which was transposed into German law through the Kreislaufwirtschaftsgesetz (KrWG) established the so-called 5-step waste hierarchy, which gives a clear preference to recycling over energy recovery and disposal of waste in landfills. Although waste avoidance and recycling are stated objectives of German waste policy, effectiveness and efficiency of the respective regulations seems to be influenced negatively by interactions with other policy instruments. Both, the internal interaction between different waste management policies as well as the external interaction between waste management policy and climate policy, seem to have a negative impact on the recycling of plastic packaging material. In order to gain insights regarding the impacts of different policy instruments on the recycling of plastic packaging waste, we conducted a case study analysis based on data gained from an online survey among German experts in the field of plastic packaging waste management and from the literature on waste management. Apparently, negative policy interactions originate from conflicting interests between the stakeholders of the different waste treatment options, i. e. recycling, thermal recovery and incineration. In the policy design stage, these conflicting interests have resulted in a regulatory flexibility that has made the recycling objective susceptible to the potentially negative effects of policy interactions. Apart from the requirement to achieve the minimum recycling quota for plastic packaging waste of 36 %, the waste management actors are flexible to choose their preferred waste treatment option once this threshold level has been achieved. In particular with regard to the recovery of low and medium grade plastic waste, economic incentives for thermal recovery and incineration seem to be much stronger than for recycling. This situation can partly be explained by the demand of energy intensive industries for plastic waste as a substitute for conventional energy sources. This trend has resulted in a considerable increase of the thermal recovery of plastic packaging waste between 2003 (2.3%) and 2010 (25.6%). With re-gard to waste incineration, the effect of the TA Siedlungsabfall (TaSi) on the build-up of incineration capacity and the economic imperative to utilize these capacities materialized in low costs for waste incineration. The massive build-up of capacities for waste incineration and RDF power plants decreased the costs for thermal recovery and made recycling less competitive. Structural changes of the packaging waste stream have also had a negative influence in recycling because the use of composite materials can render recycling technologically and economically infeasible.
Keywords: 330